2013
DOI: 10.3917/spub.134.0499
|View full text |Cite
|
Sign up to set email alerts
|

Amélioration de la qualité de la prévention de la transmission du VIH de la mère à l'enfant en Côte d'Ivoire

Abstract: Improvement collaborative approach is important for the improvement of the quality of PMTCT. However, the sustainability of the results of this approach remains the key challenge and will only be possible on the basis of a quality culture of health workers, and greater commitment of authorities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…As in this study, not all the collection tools needed to improve quality were available at all sites, or even some sites had none [13].These are the basic aspects that can report when implementing of activities.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…As in this study, not all the collection tools needed to improve quality were available at all sites, or even some sites had none [13].These are the basic aspects that can report when implementing of activities.…”
Section: Discussionmentioning
confidence: 87%
“…Mother-to-child transmission of HIV infection remains a major public health problem, particularly in developing countries, particularly in sub-Saharan Africa, where transmission remains high due to lack of access to basic PMTCT services (HIV testing and counselling, family planning, infant feeding counselling and support, and ARV prophylaxis) for the majority of women and children 13,14 . This contributes to preventing the achievement of the elimination of mother-to-child transmission of HIV (eMCT) [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the results of use of continuous QI to merge content and process to improve performance. 7-9 The percentage of MBPs receiving the standard care package improved from 0% to 100% by period 4 (mean = 98.6%, SD = 22.6) (see Figure 2, graph C). The percentage of HIV-positive pregnant women and lactating mothers who received IYCF counseling at each visit improved from 45% to 100% by period 3 (mean = 93.1%, SD = 15.5) (Figure 2, Graph A).…”
Section: Discussionmentioning
confidence: 99%
“…6 Studies have suggested that QI can improve PMTCT processes and outcomes in resource-challenged health systems in sub-Saharan Africa. 7-9…”
Section: Introductionmentioning
confidence: 99%